IN VITRO ACUTE TOXICITY OF DANDELION LEAF EXTRACT (Taraxacum officinale F.H.Wigg) WITH BRINE SHRIMP LETHALITY TEST (BSLT) METHOD - Dian Mega Sugiyarto; Annisa Farida Muti; Dhigna Luthfiyani Citra Pradana; Eldiza Puji Rahmi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Toxicity is a characteristic feature of substances that can cause harmful effects. This study aimed to determine the toxicity of dandelion leaves (Taraxacum officinale F.H. Wigg) to Artemia salina Leach larvae within 24 hours. Dandelion leaves were extracted using a maceration method with 50% ethanol. The yield was 5.88%. The results showed that dandelion leaves contain alkaloids, flavonoids, steroids, triterpenoids, and phenols. Toxicity tests were performed using the Brine Shrimp Lethality Test method, where the final result was the LC50 value. Artemia salina Leach larvae were divided into five groups. Each group had ten larvae that underwent three replications. The 50%ethanolic extract of dandelion leaf concentrations in the treatment media were 50 ppm (P1), 100 ppm (P2), 150 ppm (P3), 200 ppm (P4), and 0 ppm (seawater) as the control. Probit analysis of Artemia Salina Leach mortality percentage data. The results indicated that the 50%ethanolic extract of dandelion leaves is harmful to larvae, with LC50 values of 165,223 ppm (toxic) or in the equation y = 2,114x + 0,311, with an R² value of 0,9435. Keywords: Artemia salina, BSLT, Dandelion leaf, LC50, Toxicity